2012
DOI: 10.1007/s00240-012-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Flos carthami extract against ethylene glycol-induced urolithiasis in rats

Abstract: Flos carthami (FC), also known as Carthamus tinctorius, is a traditional Chinese herbal plant that has been prescribed since centuries for treating various symptoms related to blood circulation improvement. This study aimed to investigate the effects of FC on calcium oxalate (CaOx) formation in ethylene glycol (EG)-fed rats. A total of 50 male Sprague-Dawley rats were divided into the following 6 groups: group 1, as the normal control (n = 5); group 2 received gastric gavages of starch and 0.75% EG (placebo, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…In another study, an administration of a drug containing T. terrestris to sodium glycolate fed rats produced a significant decrease in urinary oxalate excretion and a significant increase in urinary glyoxylate excretion [31]. Recently various herbal plants such as Flos carthami, Costus igneus, Tribulus terrestris and Scoparia dulcis have successfully proved as prophylactic and curative medicine for urolithiasis [32][33][34][35]. Another recent in vitro study showed that leaf extracts of I. eriocarpa possesses potent antiurolithiatic activity [36].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an administration of a drug containing T. terrestris to sodium glycolate fed rats produced a significant decrease in urinary oxalate excretion and a significant increase in urinary glyoxylate excretion [31]. Recently various herbal plants such as Flos carthami, Costus igneus, Tribulus terrestris and Scoparia dulcis have successfully proved as prophylactic and curative medicine for urolithiasis [32][33][34][35]. Another recent in vitro study showed that leaf extracts of I. eriocarpa possesses potent antiurolithiatic activity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Consideraram ainda, que a liofilização do extrato também pode ter influenciado negativamente. Micali et al (2006) Lin et al (2012), verificaram tendência hemorrágica em ratos portadores de urolitíase, induzida por etilenoglicol, e tratados por Flos carthami, embora tenha sido demonstrada a inibição de deposição de sais de CaOx. Assim, o desenvolvimento de estudos clínicos determinando a eficácia da associação de plantas medicinais no controle de urolitíases (Saleem et al, 2012) é fator determinante para o avanço das pesquisas nesta área.…”
Section: Phyllanthus Niruri: Estudos Clínicosunclassified
“…5 Significant curative effect of plants was due to various flavonoids and other antioxidant compounds present in it. 6 Studies had shown that supplementation of antioxidants provide cellular protection to the kidney, by inhibiting the over expression of inflammatory cytokines and improved the antioxidant status of the whole system. 7,8 Citrus fruit and their peels consist of a wide range of flavonoid compounds including Eriocitrin, Hesperidin, Naringin, Naringenin, which are known for its abilities to offer beneficial biological properties.…”
Section: Introductionmentioning
confidence: 99%